RELATIONSHIP BETWEEN THE VO2 MAX AND INDICATORS ANTHROPOMETRIC OF BODY COMPOSITION IN PRACTITIONERS OF PHYSICAL EXERCISE IN ACADEMY GYM IN THE CITY OF SANTO ANTONIO DE JESUS – BA (Fiep Bulletin - online, 2016)
This study aimed to analyze the relationship between the consumption Maximum oxygen (VO2 max) and anthropometric indicators of body composition in healthy adults practitioners of aerobic exercise, aged between 19-59 years (30.61 ± 8.71) in a health club in Santo Antonio de Jesus-Ba. The sample consisted of 49 subjects, 33 (67.35%) were female with an average age of 29.30 ± 7.54 years and 16 (32.65%) were male with an average age of 33.31 ± 10.49 years, the variables were collected from physical assessments performed at the study site. Body mass were observed (kg), height (m), body mass index (kg / m²) and waist circumference (WC), as well as measure of cardiorespiratory fitness (CRF) by VO2max prediction (ml.kg .min), following the recommendations of the American College of Sports Medicine (ACSM, 2014). Descriptive statistics were used and to identify the relationship between anthropometric variables the Pearson correlation, adopting a significance level of p
Keywords: Vo2 Max. Anthropometric Indicators. Healthy Adults.